Rebudgeting in Local Governments: From Organizational Features to Political Variables - Chartady, Rachmad (Riset Akuntansi dan Keuangan Indonesia, 2021)
This study aims to test several hypotheses about potential factors that can influence rebudgeting practices in local government. The independent variables used are Budget Deviation, General Election, Employee Expenditure, Financial Condition and Gross Regional Domestic Product. This is a descriptive quantitative and correlational research. The analytical method used has three stages, namely the classical assumption test and hypothesis testing. The classic assumption test used includes the normality test, multicollinearity test, heteroscedasticity test, and linearity test, while the hypothesis test includes the partial test (t test) and the determination coefficient (R2). The results of this study indicate that employee expenditure, financial condition and GDP have a positive influence on rebudgeting. This indicates that the three variables are able to influence the rebudgeting rate by regional governments. Meanwhile, the variables of budget changes and elections have no effect on rebudgeting. This finding indicates that the value of this variable has not been able to influence the rebudgeting rate